The effect of optimal medical therapy on 1-year mortality after acute myocardial infarction. Issue 8 (29th March 2010) - Bramlage, P; Messer, C; Bitterlich, N; Pohlmann, C; Cuneo, A; Stammwitz, E; Tebbenjohanns, J; Gohlke, H; Senges, J; Tebbe, U
Abstract : Objectives: Five drug classes have been shown to improve the prognosis of acute myocardial infarction in clinical trials: aspirin, β-blockers, statins, renin angiotensin system (RAS) blockers and thienopyridines. We aimed to assess whether the benefits of combining these drugs (termed optimal medical therapy, OMT), will result in a reduction of mortality in clinical practice. Design: Nationwide registry Setting: Hospitals with a cardiology unit or internal medicine department. Patients: 5353 patients with acute myocardial infarction. At hospital discharge 89% received aspirin, 90% β-blockers, 84% statins, 81% RAS blockers, 70% a thienopyridine and 46.2% OMT. Interventions: Pharmacotherapy Main outcome measures: OR with 95% CI for mortality from myocardial infarction were calculated and adjusted for patient risk at baseline. Results: Total mortality was reduced by 74% in patients receiving OMT (adj OR 0.26; 95% CI 0.18 to 0.38) versus patients receiving one or no drug. This was consistent in subgroups defined by STEMI/NSTEMI, diabetes and gender. Mortality was also reduced in patients receiving 2–4 drugs (adj OR 0.49; 95% CI 0.35 to 0.68), diabetic patients being the only subgroup with no significant effect. Analyses on the relative importance of either component revealed that withdrawal of β-blockers (adj OR 0.63; 95% CI 0.34 to 1.16) and/or a combination of aspirin/clopidogrel (adj OR 0.59; 95% CI 0.20 to 1.17) abolished the risk reduction conferred by OMT. Conclusions: OMT over 1 year was associated with a significantly lower mortality of patients with acute myocardial infarction in clinical practice. However OMT is provided to less than half of eligible patients leaving room for substantial improvement.